2019
DOI: 10.2147/vmrr.s185159
|View full text |Cite
|
Sign up to set email alerts
|

<p>Infectious bursal disease virus in chickens: prevalence, impact, and management strategies</p>

Abstract: Infectious bursal disease (IBD), also known as Gumboro disease, is a highly contagious, immunosuppressive disease of young chickens. Although first observed about 60 years ago, to date, the disease is responsible for major economic losses in the poultry industry worldwide. IBD virus (IBDV), a double-stranded RNA virus, exists as two serotypes with only serotype 1 causing the disease in young chickens. The virus infects the bursa of Fabricius of particularly the actively dividing and differentiating lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 90 publications
4
107
1
3
Order By: Relevance
“…This is further supported by the fact that the first confirmed case of IBD was reported on a commercial farm where a live attenuated vaccine imported from the Netherlands had been used. Evidence from the literature suggests that vvIBDV strain DV86, which was first detected in the Netherlands in 1986, spread from there to various parts of the world [5].…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the fact that the first confirmed case of IBD was reported on a commercial farm where a live attenuated vaccine imported from the Netherlands had been used. Evidence from the literature suggests that vvIBDV strain DV86, which was first detected in the Netherlands in 1986, spread from there to various parts of the world [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous report suggested that for viral replication, bursa of Fabricious is the vital target organ. In acute case, bursa of Fabricious is haemorrhagic, oedematous, turgid and within 7 to 10 days turns in atrophic (Dey et al, 2019). These differentiations in clinical signs depend on the subsistence of maternal immunity, virulence of causative agent and bird's age (El-Samadony et al, 2019;Rauw et al, 2007;Hassan, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…These differentiations in clinical signs depend on the subsistence of maternal immunity, virulence of causative agent and bird's age (El-Samadony et al, 2019;Rauw et al, 2007;Hassan, 2004). In the bursa of Fabricious, the stage of B cell differentiation keeps a vital role for viral replication as the stem cell (Dey et al, 2019). Our study (95) observes that, there might be the possible difference among the bursal samples for pathogenesis of IBD were irreversible bursal follicle damage and IgM-bearing B lymphocytes and others cell damage (Rodriguez-Chavez et al, 2002), those were more severe in haemorrhagic bursa compared to oedematous and atrophied bursa which increased the sensitivity in haemorrhagic bursa compared to oedematous and atrophied bursa for IBDV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations